Laparoscopically Resected Foregut Cyst Adjacent to the Right Adrenal Gland. Issue 1 (1998) - Yamamoto, E.; Nakayama, H.; Ozaki, N.; Kitamura, Y.; Funatsuka, M.; Ueda, M.; Chikugo, K.; Hirata, A.; Kurashina, A.; Kuratsuka, H.; Nakagawa, M.; Nagaoka, S.
Abstract : A case of 49-year-old woman with a retroperitoneal undifferentiated foregut cyst attached to the right adrenal gland is reported. The bronchogenic cyst is a type of foregut cyst with a cartilage component, but in this case the multicystic tumor lacked both cartilage and gland. It is quite rare among retroperitoneal tumors and has not been reported so far to have malignant potential. The preoperative diagnosis was an adrenal benign incidentaloma, and the patient successfully underwent laparoscopic resection of the cystic tumor together with the right adrenal gland by lateral transabdominal approach. Laparoscopic surgery for a retroperitoneal tumor is problematic, however, since benignancy cannot be predicted. In laparoscopic adrenalectomy for non-functioning adrenal tumor, therefore, a differential diagnosis from retroperitoneal tumor should be given serious consideration.